MODEL PEMBELAJARAN CONCEPT SENTENCE TERHADAP KEMAMPUAN MENULIS DESKRIPSI SISWA TUNARUNGU SEKOLAH LUAR BIASA - BELLA NOERZHULANTA, WILDAN; PURBANINGRUM, ENDANG (Jurnal Pendidikan Khusus, 2018)
MODEL PEMBELAJARAN CONCEPT SENTENCE TERHADAP KEMAMPUAN MENULIS DESKRIPSI SISWA TUNARUNGU SEKOLAH LUAR BIASA Wildan Bella Noerzhulanta1 dan Endang Purbaningrum2 (Pendidikan Luar Biasa, Fakultas Ilmu Pendidikan, Universitas Negeri Surabaya) wildanbella12@gmail.com Abstract:The hearing impairment caused the speaking ability less developing and influenced toward speech ability causing some problems to the hearing impairment children?s development. One of them was little information received by the children so it had impact to their writing ability. One of the writing kinds was writing description.To solve the problem above, it needed to be done the learning which could help the hearing impairment children in writing description by noticing the hearing impairment children?s characteristics depending on learning visually. The learning model of concept sentence had several steps which were adjusted to the hearing impairment children?s characteristics such as conducting the picture teaching material, dividing class into several groups, presenting keywords related with learning material, discussion and conveying the discussion result. This research had purpose to describe the influence of concept sentence learning model in learning writing description. In this case especially writing description to the learning of Social Study.This research used quantitative approach of pre experiment kind and the research arrangement was one group pre test ? post test design.The subject of this research was hearing impairment students class VIII numbering 10 people.The research location was in SLB-B Dharma Wanita Sidoarjo. The technique of data collection was in the form of test and the technique of analysis statistic non parametric data applied the formula of Wilcoxon match pairs test.Based on the result of analysis statistic non parametric data using the formula of Wilcoxon match pairs test, it was known that Z counted was 2,80, it was greater than the Z table value with critic value 5% = 1,96. So, null hypothesis (Ho) was refused and alternative hypothesis (Ha) was accepted.The result of data analysis indicated that there was significant influence to the usage of concept sentence learning model in learning writing description to hearing impairment students class VIII in SLB-B Dharma Wanita Sidoarjo. Keywords: Concept sentence learning model, learning writing description, hearing impairment.